Ethical issues related to access to treatment for HIV/Aids in low-resource countries - bele, Paul N. de; Chigwedere, Edward (Brazilian Journal of Sexually Transmitted Diseases, 2005)
This paper examines ways that moral considerations come to bear on HIV/AIDS care and treatment in limited resource countries. We highlight vari-ous ethical issues that relate to access to antiretroviral therapy within limited resource countries as well as some of the questions that HIV/AIDS treatment programme managers have to think about when designing HIV/AIDS treatment programmes in limited resource countries in order to ensurefairness in terms of access to treatment. The paper includes recommendations on how to increase access to antiretroviral therapy in limited resour cecountries and how to overcome or minimise some of the ethical problems relating to access to care.